Kãgran: o ensino da temática indígena nas escolas e os Kaingangs no Rio Grande do Sul - Santos, Francisco Ailton dos (My University, 2022)
The culture of the gaucho indigenous peoples, especially the Kaingang ethnic group, their language, iconography and their ways of life, are the object of this dissertation. The research aims to analyze the iconographic findings, the kagrãs of this ethnic group and understand how this graphic language suffered muffled by the culture of non-Indians over time. The research was carried out from the bibliography of the gaucho writer Véra Stedile Zattera, especially on indigenous and traditionalist clothing, passing through the iconographic analyzes of Erwin Panofsky, based on the definitions of culture by Clifford Geertz and Roque de Barros Laraia. To understand aspects of ethnicity, oral interviews were carried out in the Kaingang community in Farroupilha, Rio Grande do Sul, as well as online questionnaires with teachers from public and private schools, to understand the difficulties in approaching the topic in the classroom. To support the development of this dissertation and to share the interfaces created, several products were developed: the first of them is an illustrated e-book telling the history of the indigenous gaucho ethnicities, their customs and culture, analyzing the graphics of the ancestral twins Kaingang Kainru and Kamé; the second product created is the design workshops to be reproduced in schools. To support the second product, a third product was developed, which is the production of videos teaching tips and processes of illustration and stamping. Finally, the fourth product, which is the project's digital media, created for the dissemination and sharing of the others. Thus, the set of products developed, in addition to making this research tangible, contribute to the preservation and dissemination of indigenous knowledge, emphasizing its symbolic and cultural representation for the knowledge of non-indians and recognition of indigenous people in schools. [resumo fornecido pelo autor]
A cultura dos povos indígenas gaúchos, em especial da etnia Kaingang, sua linguagem, iconografia e seus modos de vida, são objeto dessa dissertação. A pesquisa tem como objetivo analisar os achados iconográficos, os kagrãs dessa etnia e entender como essa linguagem gráfica sofreu abafamento por parte da cultura dos não índios ao longo do tempo. A pesquisa foi realizada a partir da bibliografia da escritora gaúcha Véra Stedile Zattera, especialmente sobre as vestimentas indígenas e tradicionalistas, perpassando pelas análises iconográficas de Erwin Panofsky, se amparando nas definições de cultura de Clifford Geertz e Roque de Barros Laraia. Para percepção de aspectos da etnia foram feitas entrevistas orais na comunidade Kaingang em Farroupilha, Rio Grande do Sul, bem como questionários on-line com professores de escolas públicas e privadas, para entender sobre as dificuldades na abordagem do tema em sala de aula. Para dar suporte ao desenvolvimento desta dissertação e para o compartilhamento das interfaces criadas, diversos produtos foram desenvolvidos: o primeiro deles é um e-book ilustrado contando a história das etnias indígenas gaúchas, seus costumes e cultura, analisando os grafismos dos gêmeos ancestrais Kaingang Kainru e Kamé; o segundo produto criado são as oficinas de design a serem reproduzidas nas escolas. Para dar suporte ao segundo produto, um terceiro produto foi desenvolvido, que é a produção de vídeos ensinando dicas e processos de ilustração e estamparia. Por último, o quarto produto, que são as mídias digitais do projeto, criadas para a divulgação e compartilhamento dos demais. Assim, o conjunto de produtos desenvolvidos, para além da tangibilização desta pesquisa, contribuem para a preservação e disseminação dos saberes indígenas, enfatizando a sua representatividade simbólica e cultural para conhecimento dos não índios e reconhecimento dos indígenas nas escolas. [resumo fornecido pelo autor]
Keywords: História - Rio Grande do Sul - Estudo e ensino; Índios Kaingang -Rio Grande do Sul; Iconografia; Índios - Rio Grande do Sul; Indígenas - Usos e costumes - Rio Grande do Sul; History - Rio Grande do Sul (Brazil) - Study and teaching; Kaingang Indians - Rio Grande do Sul (Brazil); Iconography; Indians - Rio Grande do Sul (Brazil); Indians - Social life and customs - Rio Grande do Sul (Brazil)